Assessment of avoidable yield losses due to insect pests in castor (Ricinus communis L.): ASSESSMENT OF AVOIDABLE YIELD LOSSES DUE TO INSECT PESTS IN CASTOR - P DURAIMURUGAN,; M LAKSHMINARAYANA, (Journal of Oilseeds Research, 2014)
Field experiments were carried out to evaluate the avoidable yield losses caused by insect pests on three castor cultivars (DCH-519, DCH-177 and 48-1) during kharif and rabi seasons of 2012-13 and 2013-14. Semilooper, tobacco caterpillar, hairy caterpillar, capsule borer and leafhopper were recorded as major pests. However, the pest succession varied with the season. The results revealed that significantly lower infestation of insect pests was observed in protected plots over unprotected plots. Higher mean seed yield of 1996 kg/ha and 1596 kg/ha was recorded from protected plots, while seed yield of 1421 kg/ha and 750 kg/ha was recorded from unprotected plots during kharif 2012-13 and 2013-14, respectively. During rabi season, higher mean seed yield of 1050 kg/ha and 927 kg/ha was recorded in protected plots, while unprotected plots recorded seed yield of 542 kg/ha and 375 kg/ha during 2012-13 and 2013-14, respectively. The mean avoidable yield losses due to insect pests on castor cultivars ranged from 17.2 to 63.3 per cent during kharif season, while the loss was higher (22.5 to 89.4%) during rabi season. Among the cultivars, DCH-519 revealed minimum avoidable yield losses due to insect pests in both kharif and rabi seasons.